Family and Community Approaches to Intimate Partner Violence: Restorative Programs in the United States - Pennell, Joan (Violence against women, 2021)
Now is the time to rethink reliance on legal intervention to end intimate partner violence (IPV). Arrest, incarceration, and family separation have fallen disproportionately on people who are Black or Brown, impoverished, or immigrant, lesbian, gay, bisexual, transgender and queer (LGBTQ). Restorative approaches bring together the persons harmed, persons causing harm, their family or community networks, or combinations of these stakeholders. Based on a U.S. national study, this article examines: What influences programs to adopt a restorative approach to ending IPV? How do programs safeguard their original vision for social change? What principles guide the programs in carrying out their work in safe and productive ways?